The Recognition of Prior Learning in Quebec: Current practices - Moss, Leah (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
The curse of being the “new, new” thing was initially hung around the neck of the current incarnation of Quebec’s ‘recognition of prior learning’ program. However, this has changed as the program has evolved into a working service for Quebec residents. This article will examine the current public offering of the recognition of prior learning program in Quebec school boards and colleges, and will briefly discuss the historical context of the program in the province of Quebec.